Effects of dietary energy levels and β-mannanase supplementation in a high mannan-based diet during lactation on reproductive performance, apparent total tract digestibility and milk composition in multiparous sows - Jin Soo Kim; Abdolreza Hosseindoust; In Kyu Ju; Xiaoguaug Yang; Su Hyup Lee; Hyun Suk Noh; Jae Hwan Lee; Byung Jo Chae (Italian Journal of Animal Science, 2018)
Two experiments were conducted to investigate the effects of dietary supplementation of β-mannanase and energy level on reproductive performance of multiparous sows during lactation. In Exp. 1, 30 multiparous sows were randomly allotted to three treatments (0400 and 800 units β-mannanase). In Exp. 2, 60 multiparous sows were fed diets containing 3250 or 3350 kcal ME/kg diet and 0 or 400 units of β-mannanase in a 2 × 2 factorial arrangement. A linear reduction in sow body weight (BW) loss during lactation was observed with increasing levels of β-mannanase. The BW change during lactation was significantly lower in sows fed high-energy diets or dietary β-mannanase. β-mannanase supplementation increased the apparent total tract digestibility of dry matter, gross energy and mannose. Diets supplemented with β-mannanase or high-energy diet increased milk fat level. Furthermore, high-energy diet increased lactose level in milk. Collectively, our data indicate that dietary inclusion of β-mannanase has the potential to improve digestibility of nutrients and reduce sow BW loss during lactation.